2021
DOI: 10.1063/5.0019564
|View full text |Cite
|
Sign up to set email alerts
|

Development of interface-/surface-specific two-dimensional electronic spectroscopy

Abstract: Structures, kinetics, and chemical reactivities at interfaces and surfaces are key to understanding many of the fundamental scientific problems related to chemical, material, biological, and physical systems. These steady-state and dynamical properties at interfaces and surfaces require even-order techniques with time-resolution and spectral-resolution. Here, we develop fourth-order interface-/surface-specific two-dimensional electronic spectroscopy, including both two-dimensional electronic sum frequency gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 140 publications
0
20
0
Order By: Relevance
“…The BOPA was based on a type I BiB 3 O 6 crystal. In our early work, , we presented a two-stage BOPA for the broadband SWIR source, in which a white light continuum was generated as a seed pulse. The two-stage BOPA caused stability issues due to the non-trivial continuum light.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The BOPA was based on a type I BiB 3 O 6 crystal. In our early work, , we presented a two-stage BOPA for the broadband SWIR source, in which a white light continuum was generated as a seed pulse. The two-stage BOPA caused stability issues due to the non-trivial continuum light.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The spectra of the ps 800 nm and the SWIR are shown in Figure S1. A detailed description of design and implementation of the BOPA were reported in our previous work. ,, The remaining portion of 0.5 mJ was used to generate a pump pulse of 400 nm by a beta-barium borate (BBO) crystal.…”
Section: Methodsmentioning
confidence: 99%
“…They found that competing charge separation processes existed in the GaAs/CuPc interface and that the space-charge field of GaAs slows down the hole injection to CuPc. Our early work demonstrated surface dynamics for p -type GaAs (100) with the development of time-resolved broadband ESFG. ,, TR-ESFG could provide time-resolved spectral information about surface structures as well as charge transfer occurring at semiconductor surfaces.…”
Section: Introductionmentioning
confidence: 97%
“…A detailed description of steady-state ESFG experiments has been reported previously. ,, Briefly, a fundamental light centered at 797 nm from a 1 kHz Ti:sapphire amplifier system (UpTek Solutions) was used. The output energy of the laser was 4 mJ per pulse with a pulse duration of 100 fs.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…A major portion of 2.0 mJ was passed through an etalon to generate a picosecond pulse of 8 cm –1 . A small portion of 1.5 mJ was used to generate a shortwave IR (SWIR) pulse from a home-built broadband optical parametric amplifier (BOPA). ,, The remaining fundamental pulse of 0.5 mJ was doubly converted with a beta-barium borate (BBO) crystal into 400 nm as a pump pulse. The time delay between the picosecond pulse and the SWIR was controlled by a motorized translation stage (Klinger).…”
Section: Experimental Sectionmentioning
confidence: 99%